Pharmacological Approaches to the Management of Aspirin-Induced Gastroduodenopathies in Patients with Ischemic Heart Disease – Traditional Strategies - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
Aspirin-induced gastroduodenopathies represent a major clinical problem in patients with ischemic heart disease who require long-term acetylsalicylic acid (ASA) therapy. Despite the proven cardiovascular benefits of ASA, its ulcerogenic potential significantly limits tolerability and adherence. Traditional pharmacological strategies to mitigate gastrointestinal (GI) injury include dose reduction, enteric-coated or buffered formulations, and the use of gastroprotective agents such as H₂-receptor blockers, proton pump inhibitors (PPIs), and prostaglandin analogs. While low-dose ASA (75–150 mg/day) effectively balances antiplatelet efficacy with a reduced risk of GI bleeding, enteric-coated and buffered forms have not fully prevented mucosal injury. PPIs remain the most effective agents for preventing and healing erosive and ulcerative lesions associated with ASA use, although long-term therapy carries risks such as Clostridium difficile infection, osteoporosis, and drug interactions. Misoprostol, a prostaglandin E₁ analog, offers comparable efficacy to PPIs in preventing NSAID- and ASA-induced gastropathies but is limited by adverse effects and poor tolerability. The optimization of therapy should consider patient risk profiles, drug interactions, and the balance between cardioprotective efficacy and gastrointestinal safety.